MATERI PELAJARAN YANG BERKUALITAS MENURUT FILSAFAT PENDIDIKAN AURELIUS AGUSTINUS - Fatlolon, Costantinus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2016)
This article intends to provide an answer to the following central question: what is valuable and interesting discipline to study accourding to Aurelius Augustinus? We want to put forth three fields of study that are useful to students, according to Augustinus philosophy of education, i.e language, morals and religion. These three areas of study should be presented to the students by the teacher with love and humility. While teaching, the teacher must be awere that the principal teacher is the teacher of the heart, i.e. being imbued by the Truth, by God himself.